Study of Bond Length and Its Effect on Guided Waves Using Fiber Optic Sensors - Kaleeswaran Balasubramaniam; Rohan Soman; Paweł Malinowski (Physical Sciences Forum, 2022)
Fiber Bragg grating (FBG) based structural health monitoring applications are used in various engineering types of damage prediction and detection analysis. FBG can serve as an effective sensor for data monitoring applications as they are more robust in harsh environmental conditions and can be embedded directly into the structure. The paper aims to study the effect of the guided wave (GW) relative magnitude based on the bond and bond length with different piezoelectric lead zirconate transducer (PZT actuator) connections. The paper compares the signal amplitudes between the directly bonded and remotely bonded FBG in the structure. A parametric study was also conducted based on signal attenuation to show the changes in the bond lengths affecting the GW. The study is conducted on the subsystem-level aluminum structure. The bond length wave attenuation-based studies were done by applying glue at various distances from the FBG sensor and glue of various spread lengths to facilitate the concept of remote and direct bonding configurations. The paper tends to predict Lamb wave modes based on the arrival time and check effective bonding type in producing quality signal amplitude with different PZT connections.